Effect of carbonated hydroxyapatite synthesis from cuttlefish shells on orthodontic relapse prevention: in silico study - Setyoko, Bondan; Verisandri, Aufa Lufhf Ambar; Damayanti, Adelia Tantri; Fitriana, Firda Ayu; Julieta, Berliant Salsabila; Noviasari, Paramita; Alhasyimi, Ananto Ali (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Relapse occurs frequently, 70â€“90% of the time, and typically compromises the outcome of orthodontic therapy. Calcium carbonate (CaCO3), which is found in cuttlefish shells, can be used to make a better biomaterial. One example is carbonated hydroxyapatite, which is very similar to human bone tissue and can stop osteoclast activity on the pressure side of the retention phase. This is a factor in orthodontic relapse, which is when the bone doesn't remodel properly. In this study, a test was done to see if carbonated hydroxyapatite (CHA) could be used as an alternative material to stop orthodontic relapse. The test was based on how the RANK-RANKL, OPG, and TGF-Î² proteins interacted with each other. Method: CHA extracted from cuttlefish shells after 6 hours of calcination at 1000Â°C. RANK-RANKL, OPG, and TGF-Î² interactions were investigated in silico using molecular docking. Result: A cuttlefish shell extract containing CHA has the potential to be used as an alternate material to prevent orthodontic recurrence. CHA chemicals can disrupt the link between RANK and RANKL and enhance OPG and TGF-Î² expression. This induces enhanced proliferation, which increases the number of osteoblasts and osteoblast differentiation while decreasing the rate of osteoclast activity. Conclusion: Cuttlefish shell with CHA extract has the potential to be used as an alternative material to prevent orthodontic relapse.